Promoting decent work in supply chains of the agrifood sector of Hass Avocado in Colombia: A Colombian MNE case study - Alzate, Isabel Cristina; Boada, Antonio; Manotas, Eva; Manotas, Eliana (Edelweiss Applied Science and Technology, 2024)
Thanks to the production massification in the world coupled with the increase in global production chains, it is urgent to review from different points of view, perspectives and sectors how supply chains adopt strategies to promote and encourage fair, equitable and decent labour guarantees. this article addresses the case of the MNE Avofruit S.A.S. BIC - Cartama, currently the principal exporter of Hass avocado in Colombia, which promotes through different strategies adopted by its corporate governance, decent work in its supply chain, as well as in that of its allies. To contextualize the reality in the productive sector, an analysis of sources in which there is data related to employment in the Colombian countryside, in addition to interviews with the staff of the company analyzed as a case study who provide information for the documentation and analysis of the case. The findings reveal that this company, being a reference in the sector, is promoting decent work in its supply chain and that of its allies, as well as encouraging fairer guarantees in the Colombian agricultural sector, becoming an example to follow for other products in the agroindustry sector.